Nickel-responsive transcriptional regulators1. Issue 9 (2nd September 2015) - Musiani, Francesco; Zambelli, Barbara; Bazzani, Micaela; Mazzei, Luca; Ciurli, Stefano
<x xml:space="preserve">Abstract</x> The structural features, metal coordination modes and metal binding thermodynamics of known Ni(ii)-dependent transcriptional regulators are highlighted and discussed.